Integración de la ética en la gestión de las personas y los medios para lograr la sostenibilidad del cambio - Pou Munt, Guillermo (2005)
Ethics is a key concept in management, yet it’s meaning is reduced to signify just goodwill. Ethics must be an important part of management, as companies should take actions based on objective and conclusive principles. Activities related to ethics should be included in all areas of the company. This is an important omission not only because decisions and actions must be guided by sound and objective principles but also because of the multiple benefits deriving from sustained and consistent work aimed at including ethics as a field of management activities and which therefore deserves management’s time and aimed at including ethics in all areas of people management within organizations. This paper will address elements and criteria on how to include ethics in company management from a general perspective and how this can add social value to communities.